2019
DOI: 10.3390/w11040661
|View full text |Cite
|
Sign up to set email alerts
|

Threshold Responses in the Taxonomic and Functional Structure of Fish Assemblages to Land Use and Water Quality: A Case Study from the Taizi River

Abstract: Biological functional traits help to understand specific stressors that are ignored intaxonomic data analysis. A combination of biological functional traits and taxonomic data ishelpful in determining specific stressors which are of significance for fish conservation and riverbasin management. In the current study, the Taizi River was used as a case study to understand therelationships between the taxonomic and functional structure of fish and land use and waterquality, in addition to determining the threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 60 publications
(85 reference statements)
1
8
0
Order By: Relevance
“…In particular, a 1% improvement in institutional quality declines the land-use change by 0.050%. This outcome is consistent with prior research [68][69][70] which points out that institutional quality encourages a decrease in land-use change. This suggests that the growth of government effectiveness and alignment with highly efficient applications could lead to a decline in the land-use change in EU13 underdeveloped countries.…”
Section: Resultssupporting
confidence: 92%
“…In particular, a 1% improvement in institutional quality declines the land-use change by 0.050%. This outcome is consistent with prior research [68][69][70] which points out that institutional quality encourages a decrease in land-use change. This suggests that the growth of government effectiveness and alignment with highly efficient applications could lead to a decline in the land-use change in EU13 underdeveloped countries.…”
Section: Resultssupporting
confidence: 92%
“…Abrupt shifts in the composition of fish communities are the result of species‐level responses to land conversion (Rhodes et al., 2008; Zhang et al., 2019). We found that fish communities in disparate biogeographic regions of the world showed marked consistency in patterns of species turnover that occurred at comparable or lower threshold levels of urbanization (1–10 times lower; Table 1) compared to agricultural land use.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for threshold responses of riverine fish communities to land use change remain primarily limited to catchment‐level scales (Paul & Meyer, 2001); whereas investigations at larger biogeographic scales are scarce (Clapcott et al., 2012; Daniel et al., 2015; Feld, 2013). Catchment studies have reported threshold values ranging up to 50% agricultural land use, beyond which fundamental shifts in fish community structure and biodiversity (e.g., species richness and index of biotic integrity) were observed (e.g., Allan, 2004; Feld, 2013; Kovalenko et al., 2014; Zhang et al., 2019). Threshold responses of fish community structure to urban land use appear less variable, and generally occur at lower levels ranging from 5% to 25% (e.g., Clapcott, Young, Goodwin, & Leathwick, 2010; Dahm et al., 2013; King, Baker, Kazyak, & Weller, 2011; Lisi et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The negative hydrological effects caused by this particular land use form are mainly manifested by reduced soil infiltration and increased surface runoff, as well as increased sediment and sources of pollutants [10,11]. From a long-term perspective, the regional urbanization process is usually accompanied by the degradation of surface water quality and aquatic ecosystems [12][13][14]. For streams, the common pollutants, e.g., nitrogen, phosphorus and heavy metals, usually increased significantly with rapid urbanization, and it has been suggested that stream water quality and aquatic ecosystems might be damaged if the proportion of impervious surfaces in watersheds reach 10%-15% [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%